Evaluación de la viabilidad técnica y financiera al implementar la tecnología ClearWELL™ en pozos productores para el control de incrustaciones (2021)
According to the geological conditions of the conventional reservoirs in Colombia, the production of water in the oil fields is usually quite high and with an increasing trend; Water, Due to its physicochemical properties and its high mineral content, coming from the producing formations, it usually brings with it problems such as corrosion and incrustation in pipes, well-installed facilities and surface production facilities. The different operating companies seek to use prevention and control methods in the face of corrosion and incrustation phenomena, for this, companies such as Delrio S.A.S, present proposals as a solution to this search. The current project was developed with the purpose of evaluating the technical and financial viability of the implementation of ClearWellTM technology in producing wells, according to the physicochemical properties of the fluids and production parameters, as a non-intrusive proposal for the prevention and control of fouling.